APPLICATION OF LINE GRAPHS AND COMPLETE HAMILTONIAN GRAPHS - SARMA, S.VENU MADAVA; KUMAR, T.V.PRADEEP (IJRDO -JOURNAL OF MATHEMATICS, 2017)
In 1856, Hamiltonian introduced the Hamiltonian Graph where a Graph which is covered all the vertices without repetition and end with starting vertex. In this Paper I would like to prove that Let “G” be a Complete graph with at least four vertices. Then, the line graph “L(G)” is Complete Hamiltonian if and only if “G” is dominating trailable.